Infrastructure and regional development in the People's Republic of China - Zhijun Zhao; Toshiki Kanamori (Asian Development Bank Institute (ADBI), 2007)
This paper investigates the relationship between infrastructure and rural economic development. It begins by reviewing the progress of Chinese economic and rural reform and analyzes the challenges faced by the government of the People's Republic of China (PRC). Then, based on the review, an endogenous growth model is created to show the channel and mechanism of public infrastructure impacting production and consumption. Next, an empirical study is carried out in order to identify the role of different kinds of infrastructure in rural development. The paper also discusses the interaction between institutional arrangement (soft infrastructure) and hard infrastructure. Finally, some suggestions and implications beneficial to the rural development of the PRC are drawn from theoretical and empirical studies.
Keywords: R11; Q18; P25; 330; Regionale Entwicklung; Institutionelle Infrastruktur; Neue Wachstumstheorie; Schätzung; China